Analysis of injury mechanisms in head injuries in skiers and snowboarders - Bailly, N.; Afquir, S.M; Laporte, J.-D.; Melot, A.; Savary, D.; Seigneuret, E.; Delay, J.-B.; Donnadieu, T.; Masson, C.; Arnoux, P.-J. (Medicine & Science in Sports & Exercise, 2017)
Purpose: Mechanisms of injury and description of head impacts leading to traumatic brain injury (TBI) in skiers and snowboarders have not been extensively documented. We investigate snow sport crashes leading to TBI 1) to identify typical mechanisms leading to TBI to better target prevention measures and 2) to identify the injury mechanisms and the head impact conditions.